1991
DOI: 10.1111/j.1365-2559.1991.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Plexiform spindle cell naevus: a distinctive variant of plexiform melanocytic naevus

Abstract: Twelve cases of a unique plexiform melanocytic naevus that we have termed plexiform spindle cell naevus are reported. The lesions affected young individuals (mean age 22.5 years) of both sexes and were most frequently located on the shoulders and back. The lesions clinically were slightly raised and blue or darkly pigmented, suggesting blue naevus. Histologically these tumours had a symmetrical wedge-shaped configuration, as seen in typical Spitz naevus, with the apex directed toward the deep reticular dermis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…In mature forms of Reed nevi, cells are arranged in elegant elongated fascicles parallel to the epidermis [8,9,114]. Cells are mostly spindle and rich in pigment, which is also present in the epidermis in the keratinocytes and in the dermis inside numerous melanophages.…”
Section: Reed Nevus Vs Melanoma With Features Of Reed Nevusmentioning
confidence: 99%
“…In mature forms of Reed nevi, cells are arranged in elegant elongated fascicles parallel to the epidermis [8,9,114]. Cells are mostly spindle and rich in pigment, which is also present in the epidermis in the keratinocytes and in the dermis inside numerous melanophages.…”
Section: Reed Nevus Vs Melanoma With Features Of Reed Nevusmentioning
confidence: 99%
“…The DPN is a variant of benign melanocytic nevus with clinical and histologic features that may be alarming and can be mistaken for vertical growth phase, nodular malignant melanoma (NMM; refs. [1][2][3][4]. In some cases, only histologic features together with clinical follow-up information can confirm that a lesion was truly benign.…”
mentioning
confidence: 99%
“…Barnhill et al 2,3 reported a histomorphologically similar melanocytic lesion using the term plexiform spindle cell nevus. However, the plexiform spindle cell nevus is more plaque-like and surrounds the superficial neurovascular plexus.…”
mentioning
confidence: 99%
“…1,2,5,[7][8][9][10] Estimates exist that, depending on the criteria used for classification, misdiagnoses as melanoma occur in 29-40% of the cases. 1,4,5 The opposite, that is taking advanced melanomas as deep penetrating nevi may also occur.…”
mentioning
confidence: 99%